Literature Review: Perbedaan Budaya Negara Individualis dan Kolektivis Antesenden Manajemen Privasi di Jejaring Sosial (SNS) - Sonia Bella Prastika; Mutia Husna Avezahra (Universitas Negeri Malang, 2023)
In this Literature Review, we examine the psychological antecedents of privacy management strategies on social networking (SNS) sites and expand our understanding of collective privacy management by using articles that review various individualistic and collectivistic countries. In these countries, there are differences regarding privacy management in social networks (SNS). Articles were collected using the systematic review method through a search process on Google Scholar to sort articles according to the topic of privacy management in individualistic and collectivistic countries. The results of the articles are based on predetermined categories, namely based on point results (Dutch America), (German America), (Korean Chinese America), and (Singaporean American Korean). So, in this case, it is proven that America, as an individualistic country, holds the highest privacy management power compared to collectivistic countries such as China, Korea, the Netherlands, Germany, and Singapore. In addition, the authors found that, in general, users' privacy attitudes, social norms, and self- or collective control beliefs substantially predicted the adoption of privacy management strategies. These findings contribute to explaining the adoption of behavioral privacy management strategies by users. We conclude with global and country-specific recommendations regarding future privacy designs for privacy management. AbstrakTujuan penulisan artikel ini adalah pemeriksaan anteseden psikologis dari strategi manajemen privasi di situs jejaring sosial (SNS) dan memperluas pemahaman untuk manajemen privasi kolektif. Menggunakan artikel yang mengulas Negara individualistik dan kolektivistik. Terlihat adanya perbedaan pada Negara tersebut mengenai manajemen privasi di jejaring sosial (SNS). Artikel dikumpulkan menggunakan metode systematic review melalui proses pencarian pada google scholar dan memilah artikel yang sesuai dengan topik manajemen privasi di Negara individualistik dan kolektivistik. Hasil artikel berdasarkan kategori yang telah ditentukan yaitu berdasarkan point result (Amerika Belanda), (Amerika Jerman), (Amerika Cina Korea) (Amerika Singapura Korea). Sehingga dalam hal ini terbukti bahwa Amerika sebagai Negara individualistik memegang kekuasaan manajemen privasi tertinggi dibandingkan dengan Negara koletivistik seperti cina, korea, belanda, jerman dan singapura. Selain itu, penulis menemukan bahwa secara umum sikap privasi pengguna, norma sosial, dan keyakinan kontrol diri atau kolektif secara substansial memprediksi penerapan strategi manajemen privasi. Temuan ini berkontribusi pada penjelasan penerapan strategi manajemen privasi perilaku oleh pengguna.